Important Aspects of the Development of Foreign Economic Activities - Jasurbek Ataniyazov (Peerian Journals Publishing, 2023)
The article describes the need and development of foreign economic activity, topical issues of increasing the export potential of the national economy and the main risks that may affect the development of foreign economic activity in the current situation on the world market. The purpose of the study is to identify the main strategic objectives for strengthening the integration of the national economy into the international financial system. And also this article describes the comparative advantage of the Republic of Uzbekistan in integrating into the world economy in terms of its competitiveness at the regional and global levels, largely related to the development and implementation of foreign economic policy. The authors used the following research methods: as grouping, abstraction, comparative analysis, structural analysis and scientific forecasting. The conclusion is made on the analysis of trends in the country's foreign trade turnover, current scientific proposals and practical recommendations on the main directions of development of foreign economic activity in the future
Keywords: export; import; international financial system; international capital market